Chopy Easy / Aina Najwa Mohd Husainy … [et al.] - Mohd Husainy, Aina Najwa; Mohd Sulaiman, Nur Hafizah Hatiqah; Mohd Lam Shah, Nurshahzalina; Yusri, Norsyahira (Faculty of Business and Management, 2020)
When technology is increasingly evolving, people have a relatively strong demand for food. Chopping board is one of the important cooking tools to prepare food with a perfect look. Chopping board was developed that not only preserves the role of slicing food from conventional chopping board, but also save the kitchen countertop or table from scratches. In addition, by using the chopping board, housewives or chefs can conveniently position the chopped food materials in drawers in conjunction with the storage and dispensing principles to eliminate the constraint of inadequate space or avoid separate food materials from mixing together in the same dish, whereas the auxiliary cooking configuration gives users flexibility in the process of using peeler. The typical chopping board has a basic structure and acts as a chopping board for food ingredients that are typically put in separate dishes and placed on the countertop in the kitchen. As modern kitchen room is small, when a number of dishes are put on the kitchen countertop, it is relatively uncomfortable. The innovation is a further enhancement of conventional chopping boards to improve the cooking environment and solve the problem of putting an enormous number of dishes in such a small area, enhancing the structure and restoring the faults of traditional chopping boards. It is a functional result of different functions that increases space usage with the innovative and creative nature to reduce the inconvenience in cooking. Therefore, the body of the chopping board have the interlayers. Interlayers are used according to customer specifications to change the storage space so that the chopped or peeled food products can be further sorted and placed in drawers. Food materials can be quickly taken from the cooking drawers. However, in the hustle and bustle of everyday life, the bland and inflexible use of cooking equipment invariably makes people feel restless about cooking. The multifunction and diversified mix is supposed to bring pleasure of cooking in life with the innovative nature of multi-purpose chopping boards.